Regulatory Arrangement in the Walfare Sector using the Omnibus Law Method - Vivi Oktaviani Pulukadang; Novendri Mohamad Nggilu; Fence M. Wantu (Nagari Law Review, 2021)
Pancasila and the 1945 Constitution describe Indonesia as a welfare state. In order to cause this happen, many regulations have been formed, which to this date have not been able to bring comfort and splendor in implementing the welfare of the Indonesian people. The number of regulations has actually brought Indonesia to the brink of regulatory obesity and resulted in ineffective regulations in the welfare sector. This study aims to provide an overview of solutions to various welfare problems in Indonesia through regulatory arrangement using the omnibus law method. It represents a normative study using a legal approach and conceptual approach. The results indicate that the application of the omnibus law method can be an innovative alternative without violating the Indonesian legal system. It is because the application of the omnibus law method begins with a legal transplant, which comprises several provisions: The omnibus law approach pattern is limited per sector/theme; (2) simplification of law using the omnibus law method is carried out by measuring the relevance of a regulation with basic criteria; (3) the formation of regulations using the omnibus law method using comprehensive, multidisciplinary and multi-sector approach; (4) the application of the omnibus law method as a whole must be oriented to Pancasila, the 1945 Constitution and Law Number 12 of 2011. Regulatory arrangement with the omnibus law method can not only provide effectiveness but also overcome regulatory obesity for more satisfactory legal system and administration of welfare.